1955
DOI: 10.1161/01.res.3.6.604
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Membrane Potentials and Contractility of Normal Rat Atrium and the Effects of Temperature, Tension and Stimulus Frequency

Abstract: Simultaneous recording of membrane potentials and contractility in isolated rat atria by means of intracellular micro-electrodes and a sensitive strain gage has been used to establish the normal characteristics of the tissue as well as effects of temperature, stimulus frequency and initial tension on muscle. Preliminary correlations between duration of the action potential and the degree of contraction indicate that the rate of repolarization is of major importance in determination of the contractile response.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
17
0

Year Published

1959
1959
1984
1984

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(19 citation statements)
references
References 2 publications
2
17
0
Order By: Relevance
“…They found that in the range 38-19', the action potential, particularly the plateau, became longer as the temperature fell. The same observation was also made by Hollander and Webb (1955). Marshall (1957) observed the same change in the transmembrane potential of single fibres of the rabbit atrium; the duration of the action potential rose from 240 msec.…”
Section: Discussionsupporting
confidence: 74%
“…They found that in the range 38-19', the action potential, particularly the plateau, became longer as the temperature fell. The same observation was also made by Hollander and Webb (1955). Marshall (1957) observed the same change in the transmembrane potential of single fibres of the rabbit atrium; the duration of the action potential rose from 240 msec.…”
Section: Discussionsupporting
confidence: 74%
“…The later depressive effect of high filling pressures may be related to the fact that substantial lowering of the membrane potential reduces the availability of the sodium-carrying 'spike' mechanism (Weidmann, 1955). Although neither Dudel & Trautwein (1954) nor Hollander & Webb (1955) were able to detect any change in the height or duration of the cardiac action potential on moderate stretching, the observation of the former authors that the action potential of Purkinje fibres was diminished by excessive stretching is in keeping with this view. Such effects might well appear earlier in normal and abnormal pace-makers which must depolarize spontaneously at a more rapid rate than other cardiac muscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has long been known that distension of mammalian atrial tissues including the sinoatrial (SA) node produces an acceleration of heart rate (BAINBRIDGE,1915;SASSA and MIYAZAKI, 1920;SCHERF et al, 1949;HOLLANDER and WEBS, 1955;BLINKS, 1956;PATHAK, 1959) which appears to be due to a direct action on the pacemaker cells. Brooks and his coworkers LANGE et al, 1966) studied the effect of stretch on the discharge rate of in situ or isolated mammalian SA nodal region and suggested that the stretch-induced acceleration of pacemaker activity is mediated by a lowering of membrane potential caused by an increase in Na permeability, while extrinsic nerves are not essential to this reaction.…”
mentioning
confidence: 99%